1995
DOI: 10.5144/0256-4947.1995.120
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Diabetic Nephropathy Among Saudi Patients with Noninsulin-Dependent Diabetes Mellitus

Abstract: There were no studies on the different stages of diabetic nephropathy in Saudi Arabia, particularly the earliest stages. We have therefore investigated the frequency of occurrence of varying degrees of proteinuria including microalbuminuria in noninsulin-dependent diabetes mellitus (NIDDM) Saudi patients as well as the correlation of varying degrees of proteinuria with other diabetic complications and risk factors. One hundred and twenty-five NIDDM patients were studied. Fifty-seven were males and 68 were fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
20
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 30 publications
9
20
0
Order By: Relevance
“…Controlling FBS is important in the follow-up and control of diabetes patients. HbA1c was not correlated statistically with albumin concentration in urine, which is consistent with a similar finding in the study conducted by Huraib et al 21 The Diabetes Control and Complications Trial 22 study found that for every 1% reduction in HbA1c, there was a 28% reduction in nephropathic complications in type 1 diabetes, as compared to 34% in type 2 diabetes at 12 years' follow-up. The duration of diabetes was another variable that correlated with albuminuria (P=0.012).…”
Section: Discussionsupporting
confidence: 80%
“…Controlling FBS is important in the follow-up and control of diabetes patients. HbA1c was not correlated statistically with albumin concentration in urine, which is consistent with a similar finding in the study conducted by Huraib et al 21 The Diabetes Control and Complications Trial 22 study found that for every 1% reduction in HbA1c, there was a 28% reduction in nephropathic complications in type 1 diabetes, as compared to 34% in type 2 diabetes at 12 years' follow-up. The duration of diabetes was another variable that correlated with albuminuria (P=0.012).…”
Section: Discussionsupporting
confidence: 80%
“…Studies in Hong Kong revealed a prevalence of 13.4% (13) and 22.7% in young diabetic patients (14). A study by Huraib et al in Saudi Arabia denoted a prevalence of microalbuminuria of 16.8% (15). In Kuwaiti individuals with Type 2 diabetes, the prevalence of microalbuminuria was 27.3% (16).…”
Section: Discussionmentioning
confidence: 99%
“…There are tremendously increasing trends in the incidence of diabetes and DN, signaling a medical catastrophe in dialysis units which results in a greater consumption of economic resources 34. In Saudi Arabia alone, approximately 11 000 patients have ESRD, and 20% is due to diabetes 45. The cost of care with dialysis in Saudi Arabia amounts to US$14 000 per patient per year and the total economic burden exceeds US$540 million 6.…”
mentioning
confidence: 99%